2000
DOI: 10.1038/sj.bjp.0702977
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide‐ and vasoactive intestinal polypeptide‐containing neurones in human gastric fundus strip relaxations

Abstract: 1 The morphological pattern and motor correlates of nitric oxide (NO) and vasoactive intestinal polypeptide (VIP) innervation in the human isolated gastric fundus was explored. 2 By using the nicotinamide adenine dinucleotide phosphate hydrogen (NADPH)-diaphorase and speci®c rabbit polyclonal NO-synthase (NOS) and VIP antisera, NOS-and VIP-containing varicose nerve ®bres were identi®ed throughout the muscle layer or wrapping ganglion cell bodies of the myenteric plexus. NOS-immunoreactive (IR) neural cell bodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
77
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 49 publications
7
77
0
1
Order By: Relevance
“…Peptide mediators such as substance P, pituitary adenylate cyclase-activating polypeptide, and VIP (10,25,29,30,51) are released at higher frequencies of electrical field stimulation (EFS) of enteric and autonomic nerves. We chose EFS stimulus parameters (50 V/cm, 0.5 ms, 5 pps) that minimize the release of peptide mediators.…”
mentioning
confidence: 99%
“…Peptide mediators such as substance P, pituitary adenylate cyclase-activating polypeptide, and VIP (10,25,29,30,51) are released at higher frequencies of electrical field stimulation (EFS) of enteric and autonomic nerves. We chose EFS stimulus parameters (50 V/cm, 0.5 ms, 5 pps) that minimize the release of peptide mediators.…”
mentioning
confidence: 99%
“…Most mechanical and electrical properties in human GI tract have been investigated using electrogastrograph (EGG) and ultrasonography (Hocke et al, 2009;Matsumoto et al, 2009), although several in vitro GI motility studies have been reported (Tonini et al, 2000;Farrelly et al, 2003;Severi et al, 2006;Wang et al, 2007). In this in vitro study, we first characterized mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…Isoproterenol (ISO) and nitric oxide (NO) produce membrane hyperpolarization, decrease slow wave, and then inhibit contraction via activation of adenylate and guanylate cyclase in GI tract (Ozaki et al, 1992;Jin et al, 1993;Smith et al, 1993;Severi et al, 2006). Especially, NO is recognized as a neurotransmitter of nonadrenergic non-cholinergic (NANC) nerves in the myenteric plexus throughout the GI tract and is responsible for gastric receptive relaxation (Ozaki et al, 1992;Jin et al, 1993;Smith et al, 1993;Tonini et al, 2000). In addition, sodium nitroprusside (SNP), known NO-releasing compound, is reported to stimulate guanylate cyclase and then increase intracellular guanosine 3',5'-cyclic monophosphate (cGMP) levels, while forskolin (FSK) to stimulate adenylate cyclase and then adenosine 3',5'-cyclic monophosphate (cAMP) levels in many smooth muscles, including GI tract (Katsuki et al, 1977;Huizinga et al, 1991;Ozaki et al, 1992;Jin et al, 1993;Smith et al, 1993;Severi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Peptides such as VIP and PACAP (53) would play a role in the relaxation of some areas, including the gastric fundus and colon (54,55). Also gases such as CO (56,57) or H 2 S (58,59) are potential inhibitory neurotransmitters or neuromodulators.…”
Section: Other Neurotransmitters/ Neuromodulatorsmentioning
confidence: 99%